El desarrollo del lenguaje oral a través de la inteligencia musical en niños de 3 a 4 años de la Escuela de Educación Básica Benjamín Franklin, de la ciudad de Riobamba, periodo 2021 - Guanga Andino, Olga Mercedes (2022)
The study "The development of oral language through musical intelligence in 3-4 - year- old children from the Benjamin Franklin School of Basic Education, in Riobamba city, period 2021", is intended to determine the importance of musical intelligence in the oral language development. In this aim, an information analysis was carried out on the study variables, which was taken from duly validated primary and secondary sources; as well as from a field study throughout the interaction with those children, their teachers, and parents, to determine the influence of musical intelligence on the oral language development. The research techniques and tools used throughout the study account for a mixed (qualitative-quantitative) non-experimental research design, which allowed to make up three instruments for collecting data such as a questionnaire that was applied to teachers, a survey applied to teachers and parents, and thus, the observation sheet which were previously reviewed and validated for a later application to the study participants during the research process. From study results, data analysis, and interpretation, it was concluded that musical intelligence contributes to children’s-oral language development since children’s musical intelligence let to link this natural aptitude to favorable learning environments created for children’s cognitive and oral language development.